2018
DOI: 10.1186/s40557-018-0254-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of teacher’s working conditions on voice disorder in Korea: a nationwide survey

Abstract: BackgroundKorean teacher’s working conditions are deteriorating. There is concern about the deterioration of teachers’ health and voice disorder is one of the most common problems. Teacher’s vocal health is important for them and their students. The aim of the present study was to investigate working conditions that may affect voice disorders.MethodsIn all, 79 primary and secondary schools were randomly selected for a nationwide school system survey (N = 3345). In 64 schools, 1617 (48.3%) teachers participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 47 publications
2
26
0
8
Order By: Relevance
“…Teachers have decreased job performance due to voice issues [12]. When these voice issues persist, they are more likely to experience leave of absence [13] or sick leave [4]. Moreover, more teachers tend to resign more frequently due to vocal issues [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers have decreased job performance due to voice issues [12]. When these voice issues persist, they are more likely to experience leave of absence [13] or sick leave [4]. Moreover, more teachers tend to resign more frequently due to vocal issues [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluating risk factors associated with the prevalence of voice disorders have reported that voice disorders are related to work environment [12,16,17,18,19], overall health [3,18,20,21,22], and psychological factors [2,23] as well as personal factors such as sociodemographic factors [13,20] and voice overuse [16]. Therefore, it is necessary to identify factors causing voice disorders to teachers in various dimensions and manage them to prevent these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Es válido reconocer también que, en algunos de los estudios citados, las variables como carga, duración de las clases, número de estudiantes, no fueron variables significativamente correlacionadas con el daño vocal, específicamente al referirse a docentes de nivel superior (Polacow, De Lima, Abranches, & De Lima, 2016), (Lee, Kim, & Lee, 2018), ver Tabla 4.…”
Section: Los Factores Organizacionalesunclassified
“…Apesar do enorme impacto econômico observado, estimado em um milhão de dólares por ano, os autores ressaltam que o custo real provavelmente seria maior se outros fatores como despesa com professores substitutos e impactos em atividades não relacionadas ao trabalho fossem considerados 3 . Os autores mencionam que o presenteísmo gera custos ainda maiores e também tem sido preocupante nas escolas, pois os professores permanecem no exercício da docência mesmo sem condições vocais para cumprir suas tarefas 3,4 . Na medida em que os professores continuam usando a voz sem descanso, os distúrbios vocais tornam-se mais frequentes e crônicos 4 .…”
unclassified
“…Os autores mencionam que o presenteísmo gera custos ainda maiores e também tem sido preocupante nas escolas, pois os professores permanecem no exercício da docência mesmo sem condições vocais para cumprir suas tarefas 3,4 . Na medida em que os professores continuam usando a voz sem descanso, os distúrbios vocais tornam-se mais frequentes e crônicos 4 .…”
unclassified